The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/v14030470
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Prior Infection versus Prior Vaccination on Vaccine Immunogenicity against Influenza A(H3N2) Viruses

Abstract: Prior vaccination can alternately enhance or attenuate influenza vaccine immunogenicity and effectiveness. Analogously, we found that vaccine immunogenicity was enhanced by prior A(H3N2) virus infection among participants of the Ha Nam Cohort, Viet Nam, but was attenuated by prior vaccination among Australian Health Care Workers (HCWs) vaccinated in the same year. Here, we combined these studies to directly compare antibody titers against 35 A(H3N2) viruses spanning 1968–2018. Participants received licensed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…96 For influenza B, however, estimates were comparable with their main findings when the analysis was restricted to those patients with no documented influenza B infection in the previous season. 96 41 (49%) of 83 studies were eligible for inclusion in the meta-analysis (appendix pp [10][11][12]. These studies reported a total of 85 type-specific or subtype-specific allage estimates: 19 (23%) for influenza A(H1N1)pdm09, 30 (36%) for influenza A(H3N2), 22 (26%) for influenza B (lineage not specified), five (4%) for influenza B/ Victoria, and nine (11%) for influenza B/Yamagata (figures 2-4 and table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…96 For influenza B, however, estimates were comparable with their main findings when the analysis was restricted to those patients with no documented influenza B infection in the previous season. 96 41 (49%) of 83 studies were eligible for inclusion in the meta-analysis (appendix pp [10][11][12]. These studies reported a total of 85 type-specific or subtype-specific allage estimates: 19 (23%) for influenza A(H1N1)pdm09, 30 (36%) for influenza A(H3N2), 22 (26%) for influenza B (lineage not specified), five (4%) for influenza B/ Victoria, and nine (11%) for influenza B/Yamagata (figures 2-4 and table 2).…”
Section: Resultsmentioning
confidence: 99%
“… 5 A 1999 review of ensuing immunological studies identified that roughly half of published serological studies reported reduced post-vaccination antibody titres against A(H3N2) in people who had received multiple influenza vaccinations compared with those who had received a single influenza vaccination. 6 Several subsequent studies have shown diminishing post-vaccination antibody responses 7 , 8 , 9 , 10 , 11 and diminishing vaccine effectiveness 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 as the number of previous vaccines an individual has been given increases.…”
Section: Introductionmentioning
confidence: 99%
“…The Low Dimensionality of Antibody-Virus Interactions Empowers Matrix Completion Given the vast diversity of antibodies, it is easy to imagine that serum responses cannot inform one another. Indeed, many factors including age, geographic location, frequency/type of vaccinations, and infection history shape the antibody response and influence how it responds to a vaccine or a new viral threat (Kim et al, 2012;Fonville et al, 2014;Thompson et al, 2016;Gouma et al, 2020;Fox et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Using the age of each subject, these landscapes can quantify how immune imprinting throughout childhood shapes the subsequent antibody response (vinh et al, 2021). In addition, given the growing interest in universal influenza Vaccines capable of inhibiting diverse variants, these high-resolution responses will power studies examining the breadth of the antibody response not just forward in time against newly emerging variants, but also backwards in time to assess how rapidly immunity decays (Carter et al, 2016; Boyoglu-Barnum et al, 2021; Fox et al, 2022). We found that serum potency (the minimum HAI titer against a set of viruses) decreases for more distinct viruses [Figure 7B], as was shown for monoclonal antibodies (Creanga et al, 2021; Einav and Cleary, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst results may differ for a highly seronegative population, in our study, restricting analyses to those participants who had HI titres < 40 at baseline did not alter findings with similar results for children and adolescents with and without obesity. Prior vaccination or infection may potentially influence subsequent vaccine responses [ 31 ] and may provide cross-protective immunity against future novel influenza virus exposure [ 32 ]. Our study did not examine cross-protection against non-vaccine strains, however, we did compare seroprotection between participants who had ( n = 20) and had not ( n = 24) received a prior recent influenza vaccine and found similarly high levels of seroprotection.…”
Section: Discussionmentioning
confidence: 99%